Cover Feature: Microwave‐Assisted 1, 3‐Dipolar Cycloaddition of Azomethine Ylides to [60]Fullerene: Thermodynamic Control of Bis‐Addition with Ionic Liquids Additives (Eur. J. Org. Chem. 25/2021). Issue 25 (24th June 2021) - Martinis, Estefanía M.; Montellano, Alejandro; Sartorel, Andrea; Carraro, Mauro; Prato, Maurizio; Bonchio, Marcella
Abstract : The Cover Feature shows a kaleidoscopic vision of the frontier empty orbitals of [60]fulleropyrrolidine embracing diverse [6, 6] bonds, which poses a severe regioselectivity challenge for further ylide cycloaddition, resulting in a multitude of polyfunctionalization products. A combined kinetic and mechanistic study is reported to interrogate the thermodynamic drivers, leading to stable fulleropyrrolidine bis‐adducts, using MW‐assisted heating and ionic liquids additives. More information can be found in the Full Paper by M. Carraro, M. Prato, M. Bonchio et al.